2022
DOI: 10.4103/ijt.ijt_85_22
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Premature Hair Graying Treated with a Topical Formulation Containing α-Melanocyte-Stimulating Hormone Agonist (Greyverse Solution 2%)

Abstract: With aging, hair graying is a common sign resulting from complex regulation of melanogenesis. Multiple factors control the stimulation of melanogenesis at the level of the hair follicle, including melanin-stimulating hormone (MSH), adrenocorticotropic hormone, endothelin-1, prostaglandins, leukotrienes, neutrophils, fibroblast growth factor, nitric oxide, catecholamines, Vitamins, and minerals. Premature hair graying (PHG) has a major impact on the cosmesis, self-credibility, and social life of the affected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[13][14][15] There have also been studies where topical palmitoyl tetrapeptide 20, a biomimetic biopeptide of MSH, has been effective in converting of gray hair to black hair. 16 The mainstay of treatment of PGH is actually camouflaged by hair colorants. Hair colorants can be temporary textile dyes, natural dyes like henna or semipermanent hair colours.…”
Section: Managementmentioning
confidence: 99%
“…[13][14][15] There have also been studies where topical palmitoyl tetrapeptide 20, a biomimetic biopeptide of MSH, has been effective in converting of gray hair to black hair. 16 The mainstay of treatment of PGH is actually camouflaged by hair colorants. Hair colorants can be temporary textile dyes, natural dyes like henna or semipermanent hair colours.…”
Section: Managementmentioning
confidence: 99%
“…The graying of hair, which results from the loss of melanin‐producing cells, increases with age (Triwongwaranat et al, 2019), similar to the loss of teeth. Premature gray hair (PGH) development is potentially linked to genetics, disorders such as progeria and pangeria, oxidative stress, vitamin deficiencies, and certain drugs (Chavan, 2022; Daulatabad et al, 2016). A previous study revealed a decrease in the level of tyrosinase‐related protein (TRP)‐2 (a melanocyte marker) in gray hair (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%